Synchronous switch in diet and hunting habitats as a response to disappearance of snow cover in Tengmalm´s Owl Aegolius funereus - Jacobsen, B. V.; Sonerud, G. A. (Ornis Fennica, 1993)
To test the hypothesis that the snow-dependent diet switch in Tengmalm's Owl Aegolius funereus is caused by a simultaneous habitat shift, we studied seasonal changes in prey availability and the selection of major prey and habitattypes by two radio-equipped nesting males. Whentheground was completely snow-covered, bankvoles Clethrionomys glareolus were the commonest prey, and the owls hunted more in forest than could be expected from random use. When snow-free ground appeared, the owls switched their prey and habitat; field voles Microtus agrestis and root voles M. oeconomus became the commonest prey, and clear-cuts and forest were usedin proportion to availability . Snap-trapping showed that bank voles were commoner in forest than in clear-cuts, while field and root voles occurred almost only in clear-cuts . Snow-tracking showedthat long smallmammal trails (> 1 m) were commonest in forest, short trails (